From nucleated to ex vivo manipulated stem cells – an updated biological and clinical synopisis - Balint, Bela; Pavlovic, Mirjana; Todorovic, Milena (Medical Word, 2020)
Hematopoietic stem cells (SCs) are responsible for the production and replacement (proliferation) of an extensive quantity of functionally competent blood cells (differentiation) during the entire life, while simultaneously maintaining the ability to reproduce themselves (self-renewal). A complex network of interactive substances and factors organize and protect the survival, maturation and multiplication of SCs. Hemobiological events in the bone marrow (BM) are synchronized and balanced by the extracellular matrix and microenvironment provided by stromal cells. These cells – including macrophages, fibroblasts, dendritic, endothelial and other cells – stimulate SCs by producing specific hematopoietic growth factors. Other cytokines secreted by stromal cells regulate the adhesion molecules positioned on SCs, allowing them to remain in the BM or migrate to an area where the respective cell type is needed. Thus, hematopoietic SCs could be defined as cells with high proliferative capacity and extensive potential to differentiate into all blood cells or some somatic cell types (SC plasticity) – such as cardiomyocytes, myocytes, osteocytes, chondrocytes, hepatocytes, and even endothelial cells.Recent increasing clinical use of cell-mediated therapeutic approaches has resulted in increased needs for SCs, but in superior operating procedures during their ex vivo manipulations. The aim of cell harvestings is to obtain a higher SC yield and improved viability or clonogenicity. The goal of optimized cryoinvestigation protocols is to get a minimized cell damages (cryoinjury). Despite the fact that different SC collection protocols and cell freezing practice are already in routine use, a lot of questions related to the optimal SC ex vivo manipulations are still unresolved. This review summarizes fundamental knowledge and methodological approaches, and recapitulates data enabling progress on constantly evolving research frontiers in the SC area. The studies (including also our investigations) that evaluated the efficiency and safety of SC-treatment (transplants and regenerative medicine) will be also concisely presented.
Keywords: stem cells, transplantation, regenerative medicine